Impact of Diabetic Retinopathy on Health-related Quality of Life in Iranian Diabetics - Cyrus ALINIA; Seyed-Farzad MOHAMMADI; Alireza LASHAY; Arash RASHIDIAN (Tehran University of Medical Sciences, 2017)
Background: To extract utility values of diabetic retinopathy on a perfect health and perfect vision scales for Iranians with both types diabetes. Methods: In this investigation, 150 untreated patients with diabetic retinopathy consecutively were examined and interviewed in Farabi Eye Hospital, Tehran, Iran, a tertiary referral center in the Iranian health care system. Utility values based on patients-reported outcome measures, standard gamble, time trade off and visual analogue scale approaches, were estimated. Results: Considering all three utility elicitation methods were valid, diabetic retinopathy patients, on average reported the 0.95 (±0.03), 0.85 (±0.15) and 0.80 (±0.30) standard policy scale utility according to standard gamble, TTO and VAT respectively. In all three-studied approach, diabetic retinopathy had more disutility in higher levels of disease and had more disutility in the presence of both maculopathy and vasculopathy compared with one of them. Evidence show that share of macular edema in imposing disutility was maximum in early stage and exponentially decreased with advancing the severity of diabetic retinopathy. Conclusion: Study indicated utility scores in DR-experienced Iranian patients were highest with the SG and lowest with the VAT method. The proffered utility-elicitation method in Iranian patient populations could be the TTO approach. The novel model we employed for DR takes the effects of diabetic macular edema and vascularization into account separately, and can provide a better estimate of the QoL for these patients.